2020
DOI: 10.1177/0896920520966371
|View full text |Cite
|
Sign up to set email alerts
|

Detached Attachment: Burnout and Commitment among Caregivers in the Immigrant Rights Movement

Abstract: The increasing numbers of migrants and asylum seekers reaching the U.S.–Mexico border since 2014 has strained local nonprofit organizations helping them. Lack of material and human resources along with uncertain policy implementation by the government generates frustration and burnout among caregivers working in local nonprofits. Nonetheless, turnover as a result of burnout is surprisingly low. To answer why so few caregivers make efforts to help migrants and asylum seekers on the border, I analyze how caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The term emotion work was originally applied to conceptualising the everyday, ordinary management of emotions by individuals at home and in the workplace. More recently, social movement scholars have examined how activists manage their own and others' emotions in social movement contexts (Maney et al 2009;Gould 2015;Hagemann 2015;Jacobsson and Lindblom 2016;Kleres and Wettergren 2017;Santos 2020;Marquez 2021;Siegel 2021;Tuomola and Wahl-Jorgensen 2022). For instance, Hagemann comments: Emotion work, defined as active practices to regulate emotions, is .…”
Section: Emotion Workmentioning
confidence: 99%
“…The term emotion work was originally applied to conceptualising the everyday, ordinary management of emotions by individuals at home and in the workplace. More recently, social movement scholars have examined how activists manage their own and others' emotions in social movement contexts (Maney et al 2009;Gould 2015;Hagemann 2015;Jacobsson and Lindblom 2016;Kleres and Wettergren 2017;Santos 2020;Marquez 2021;Siegel 2021;Tuomola and Wahl-Jorgensen 2022). For instance, Hagemann comments: Emotion work, defined as active practices to regulate emotions, is .…”
Section: Emotion Workmentioning
confidence: 99%
“…Several activists raised the issue of needing to take a break from volunteering as a form of selfcare, which a vast body of research has demonstrated is a significant issue in activist work, particularly for activists from marginalized groups (e.g., Kennelly, 2014;Márquez, 2021;Pepin-Neff & Wynter, 2019). One man, Ned, carefully selects his volunteer experiences so that he has adequate time for self-care, I can't be a part of a volunteer effort where I am constrained or controlled as an individual.…”
Section: Self-care As Taking a Breakmentioning
confidence: 99%
“…In contrast to the sense of reassurance that Ned felt, Alicia, a mid-thirties Latina and public health professional, offers another perspective that resonates with the gendered way in which women, and especially women of color, feel guilt for stepping away from activism (e.g., Gorski, 2019;Kennelly, 2014;Márquez, 2021), I have backtracked some of that time at the market just for personal reasons and self-care, (laugh), but I am heavily invested and still supporting the group. I try to attend as-the planning meetings as much as possible.…”
Section: Self-care As Taking a Breakmentioning
confidence: 99%